(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This research paper explores the challenges and opportunities in rural India regarding education and healthcare accessibility, focusing on the role of social work in addressing these issues. It examines socio-economic factors like poverty, gender inequality, and infrastructure, and highlights the impact of government policies like the Right to Education Act and Ayushman Bharat. The study uses a social work perspective to analyze community-based interventions, advocacy efforts, and capacity-building initiatives to empower rural populations. It evaluates the effectiveness of collaborative approaches involving government agencies, NGOs, and local communities in bridging the access gap. The findings emphasize the need for culturally sensitive, participatory, and sustainable strategies to improve access to education and healthcare in rural areas. The paper offers policy recommendations and practical solutions aligned with the Sustainable Development Goals, particularly those related to quality education and good health.